THIRD PARTY AND BONA FIDE SPOUSE RIGHTS WHEN CONCLUSION OF MARRIAGE CONTRACTS IN UZBEKISTAN AND ARMENIA - Mutafyan, Ani; Ashurov, Dilshod (State and Law, 2025)
In the modern world, in parallel with the quantitative growth of marriage contracts, the risks of violating the rights of creditors, heirs, and a bona fide spouse through the conclusion of marriage contracts increases. Often, the parties conclude a marriage contract with the aim of harming the rights of third parties who are not parties to the contract, avoiding the fulfillment of existing obligations towards them. Failure by one of the spouses to notify his or her creditors of the conclusion, amendment or termination of a marriage contract may result in a violation of the rights of the other spouse. In addition, due to the absence of state registers of marriage contracts in the Republics of Uzbekistan and Armenia, there is no unified information base on the property status of spouses, which, in our opinion, very often causes the emergence of disputable situations. The purpose of the research is to study the guarantees for the protection of the rights of third parties who are not parties to the marriage contract, as well as the bona fide spouse, to identify and develop additional mechanisms, and to present relevant recommendations. As a result of a comprehensive study of the legislation, notarial and judicial practice of the Republics of Uzbekistan and Armenia, the authors managed to develop and propose guarantee solutions for the protection of rights, which can be of practical importance for notaries certifying marriage contracts, as well as serve as a basis for the future creation of registers of marriage contracts in the Republics of Armenia and Uzbekistan.
Keywords: Marriage contract; third party not party to the marriage contract; bona fide spouse; heir of the spouse; register of marriage contracts; creditors of the spouses; sole property of the spouses; joint property of the spouses; creditor's notice